Analisis Faktor-Faktor yang Mempengaruhi Konservatisme Akuntansi - Amelia Ifani; Yuliansyah Yuliansyah; Ratna Septiyanti; Ki Agus Andi (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the effect of dept to assets ratio (DAR), return of equity (ROE), firm size, institutional ownership on accounting conservatism. Method: The research population uses IDX financial reports, annual reports, and annual financial statistics for 2017-2021. The sample in this study consisted of LQ45 business actors registered on the IDX in 2017-2021. Methods of data analysis using multiple regression analysis with SPSS software tools. Result: The test results show that DAR has a negative effect on accounting conservatism, ROE has a positive effect on accounting conservatism, firm size has a negative effect on accounting conservatism, and institutional ownership has a negative effect on accounting conservatism. Subsequent studies add influencing variables related to accounting conservatism.